The Implementation of Stimulus Organism Response on Repeat Purchase Intention for fashion products on Tokopedia (Study of Generation Z in Semarang City) - Diki Febrianto Marbun; Ngatno Ngatno; Andi Wijayanto (Lafadz Jaya Publisher, 2024)
This study was conducted to examine the effect of social media interactivity on perceived utilitarian value, the influence of social media interactivity on perceived hedonic value, the influence of social media interactivity on repeat purchase intention, the influence of perceived utilitarian value on repeat purchase intention, the influence perceived hedonic value on repeat purchase intention, the role of perceived utilitarian value mediates the reliationship between social media interactivity and repeat purchase intention, the role of perceived hedonic value mediates the reliationship between social media interactivity and repeat purchase intention. This research was carried out in the Semarang City area. The sample in this study amounted to 100 generation z who shop for fashion products on Tokopedia. The analytical method used in this research is SEM with Smart PLS 3. The results of this study indicate that social media interactivity was able to create perceived utilitarian value and perceived hedonic value. It was found that there was a significant influence of social media interactivity on repeat purchase intention, an insignificant influence of perceived utilitarian value on repeat purchase intention, a significant influence of perceived hedonic value on repeat purchase intention, the role of perceived utilitarian value which was unable to mediate the relationship between social media interactivity and repeat purchase intention, and found the role of perceived hedonic value which can mediate the relationship between social media interactivity and repeat purchase intention.